PRODUKSI DAN IMPOR KEDELAI DI INDONESIA : SYSTEMATIC LITERATURE REVIEW - Permana, Faishal; Karim, Akhmad Rizqul; Hidayat, Ponendi (AGRORADIX : Jurnal Ilmu Pertanian, 2024)
This study aims to identify the factors influencing soybean production and imports, as well as to determine the necessary steps to increase soybean production and reduce soybean imports. This research is a systematic literature review. The results showed that the factors affecting soybean production are varietal selection, cultivation techniques, and planting area. Planting area is the key to increasing soybean production. Factors affecting soybean imports are economic growth, domestic consumption, and domestic production, which significantly influence the volume of soybean imports. Policies that can be implemented include increasing the planting area and providing seed assistance to increase farmers’ motivation to plant soybeans.